Exosomes in epilepsy: bridging neuroinflammation, diagnosis, and therapeutic delivery - Li, Bin; Zhu, Yanping; Chen, Lixia; Cui, Jiajia; Zhang, Zhenchang (Frontiers in Immunology, 2025)
Epilepsy, as a chronic neurological disorder marked by recurrent seizures, is closely linked to neuroinflammation and immune dysregulation. Exosomes, extracellular vesicles with potent immunomodulatory properties, have emerged as key players in mitigating epilepsy-associated inflammation by targeting glial activation and balancing pro- and anti-inflammatory cytokine release. Their ability to cross the blood-brain barrier (BBB) enables targeted delivery of anti-inflammatory cargo, such as miRNAs and proteins, offering promise for diagnosing and treating drug-resistant epilepsy. This review highlights exosomes’ dual role as biomarkers of inflammatory pathways and therapeutic vehicles for immune modulation. By suppressing neuroinflammation and restoring neuronal homeostasis, exosome-based strategies may revolutionize epilepsy management, though clinical translation requires further optimization of isolation and engineering techniques.